2001
DOI: 10.1023/a:1012242817869
|View full text |Cite
|
Sign up to set email alerts
|

Serine Proteinase Inhibitors from Eggs and Larvae of Tick Boophilus microplus: Purification and Biochemical Characterization

Abstract: The present study describes the purification, characterization, and comparison of serine proteinase inhibitors during the development of egg and larva phases of the tick Boophilus microplus. Samples were collected of eggs between the first day of hatching and the beginning of eclosion (defined as El, E2, and E3) and of larvae between the first day of eclosion and the infectant phase (defined as L1, L2, and L3). Crude extracts of the samples (2.5% w/v in Tris-HCI buffer) were analyzed by SDS-PAGE, and showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Our western blot results suggested that the calves that had been experimentally infected with ticks did not produce antibodies against serine proteinase inhibitors (in the range of 13-40 kDa). This result was in agreement with Andreotti et al (2001) and Pruett et al (2008). Lack of antibody induction against serine protease inhibitors in cattle during tick infestation may be due to the low amounts of these inhibitors introduced for immune response stimulation in the host.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our western blot results suggested that the calves that had been experimentally infected with ticks did not produce antibodies against serine proteinase inhibitors (in the range of 13-40 kDa). This result was in agreement with Andreotti et al (2001) and Pruett et al (2008). Lack of antibody induction against serine protease inhibitors in cattle during tick infestation may be due to the low amounts of these inhibitors introduced for immune response stimulation in the host.…”
Section: Discussionsupporting
confidence: 88%
“…Experimental challenges performed on animals previously immunized with tick larvae have shown that the animals acquired significant protective immunity against ticks, with reduction of the biological parameters that would favor ticks (ANDREOTTI et al, 2001;PREVOT et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…microplus (Tanaka et al, 1999). However, differing concentrations and inhibitor specificity changes have been reported between egg and larval stages (Andreotti et al, 2001; Sasaki et al, 2004). Andreotti et al showed a 69.7 and 71.3% reduction in both engorged tick number and egg weight respectively when female ticks were fed on BmTIs-immunized cattle, confirming a crucial role for BmTIs in egg production and development (Andreotti et al, 2002).…”
Section: Role Of Serine Protease Inhibitors In Tick Biologymentioning
confidence: 99%
“…BmTI-6 , a Kunitz tSPI identified in ovaries, was also expressed in tick body fat and demonstrated specific inhibitory activity against trypsin and trypsin-like proteases, such as plasmin (Sasaki and Tanaka, 2008). As for other BmTIs, BmTI-6 is suspected to play a role in controlling endogenous proteases in the egg and larval stages (Andreotti et al, 2001; Sasaki et al, 2004). …”
Section: Role Of Serine Protease Inhibitors In Tick Biologymentioning
confidence: 99%